Pengembangan Perangkat Research-Based Learning dengan Pendekatan STEM dalam Meningkatkan Metaliterasi Peserta Didik Menyelesaikan Masalah Himpunan Pasangan Berurutan - Excelsa Suli Wildhatul Jannah; Dafik Dafik; Arif Fatahillah (CGANT JOURNAL OF MATHEMATICS AND APPLICATIONS, 2021)
The ability of metaliteracy is very important in the industrial era 4.0. Metaliteracy is a comprehensive framework of thinking that goes beyond other literacies with the main literacy being information literacy. It is indicated that the metaliteracy of students is still low, it is because this literacy is still relatively new. The use of the IoT in learning is also still uneven, including the learning model used by teachers has not been able to fully support the formation of this ability. Therefore, in this study, the Research-Based Learning model which is integrated with the STEM approach (Science, Technology, Engineering, Mathematics) will be applied to solve the STEM problem of flight scheduling. Students are introduced to the application in the form of a set of sequential pairs, then with the representation of the set of points and lines a specific schedule is drawn up and includes its generalizations. The next step is how to bring STEM problem solving in learning class, then the developed RBL and STEM tools in learning to improve students' metaliteracy. From the results of the study, it was found that the RBL device with the STEM approach developed met the valid, effective, and practice criteria.